Endoplasmic Reticulum–Mitochondria Contact Sites—Emerging Intracellular Signaling Hubs - Aoyama-Ishiwatari, Saeko; Hirabayashi, Yusuke (Frontiers in Cell and Developmental Biology, 2021)
It has become apparent that our textbook illustration of singular isolated organelles is obsolete. In reality, organelles form complex cooperative networks involving various types of organelles. Light microscopic and ultrastructural studies have revealed that Mitochondria-Endoplasmic Reticulum (ER) Contact Sites (MERCS) are abundant in various tissues and cell types. Indeed, MERCS have been proposed to play critical roles in various biochemical and signaling functions such as Ca2+ homeostasis, lipid transfer, and the regulation of organelle dynamics. While numerous proteins involved in these MERCS-dependent functions have been reported, how they coordinate and cooperate with each other has not yet been elucidated. In this review, we summarize the functions of mammalian proteins that localize at MERCS and regulate their formation. We also discuss potential roles of the MERCS proteins in regulating multiple organelle contacts.